A reliable route for relieving the constraints of multi-main-phase Nd–La–Ce–Fe–B sintered magnets at high La–Ce substitution: (Pr, Nd)Hx grain boundary diffusion. (August 2020) - Liu, Yongsheng; Jin, Jiaying; Yan, Mi; Li, Meixun; Peng, Baixing; Zhang, Zhiheng; Wang, Xinhua
Abstract: Massive rare earth oxides inevitably form at high La–Ce substitution, causing inadequate liquid-phase-sintering, direct exchange coupling of ferromagnetic grains, obscure core–shell morphology and severe coercivity degradation of multi-main-phase (MMP) Nd–La–Ce–Fe–B sintered magnets. To fully exploit the abundant La–Ce for application, here we designed a facile approach, (Pr, Nd)H x grain boundary diffusion that combines the joint benefits of forming thick non-ferromagnetic grain boundary layer and PrNd-rich hardening shell, yielding a nearly threefold coercivity of 14.2 kOe with enhanced energy product of 38.5 MGOe for LaCe-40 magnet. These findings suggest a reliable recipe for relieving the main constraints of MMP Nd–La–Ce–Fe–B magnets. Graphical abstract: Massive RE oxides exist in the untreated multi-main-phase Nd–La–Ce–Fe-B magnets, leading to fuzzy GBs, directly contacted 2:14:1 phase grains and obscure core–shell morphology (a). (Pr, Nd)H x GBDP provides a new recipe for relieving above obstacles by forming thick non-ferromagnetic GB layer and PrNd-rich magnetically hardening shell (b). Above favorable microstructural and chemical characteristics after GBDP yield the highest reported to date magnetic performance with H cj  = 14.2 kOe, B r  = 12.7 kG, and ( BH )max  = 38.5 MGOe upon a high La–Ce substitution level of 40 wt% (c), together with a significant cost reduction by 32.5% compared to the commercial available LaCe-0 sintered magnet (d). Image, graphical abstract